Validation of Positioning, Lordotic Correction and Lack of Endplate Damage When using a New Expandable Articulated Lumbar Intervertebral Fusion Cage; A Cadaver Study. Issue 1 (April 2016) - Levy, Mark M.; Rigal, Julien; Morrison, Robert; Le Huec, Jean Charles; Schnake, Klaus J.
Introduction: Intervertebral lumbar fusion cages became nowadays a useful tool by preserving disc space height, retaining proper tension of ligaments and providing better anterior column support with contained bone graft. Expandable cages, a new available category, help to approach the disc space with less invasive techniques adjusting its height to the local anatomy. There's need in using cages with the widest footprint, able to expand to increase disc height up to normal correcting lordotic alignment, particularly at L4–5 and L5-S1 levels, without damaging the endplates in the process and reducing pre-stress of posterior instrumentation. A 3-dimensional articulated expandable cage was tested in cadavers to verify: its effect on positioning in the disc space, by navigating its two-linked segments in the transversal plane; its expansion without endplate violation and its resultant lordotic correction in the sagittal plane. Material and Methods: Five fresh-frozen human cadaver specimens were randomly assigned to two surgeon teams for discectomy and implantation of this new expandable titanium-alloy FLXfit cage through one-sided TLIF approach using fluoroscopy and standard spine instrumentation. No facetectomy or posterior instrumentation were performed. Every cadaver underwent a two level procedure, L2–3 and L5-S1. Each cage allowed a lordotic angled expansion of up to 10° with a dedicated cage tool. After implantation, all specimens were dissected and disc spaces incised for evaluation of positioning and endplate condition as result of expansion. Final positioning was documented with X-rays and lordotic angles were measured. Lordotic increments were calculated by level from pre and post-operatory measurements. Each surgeon rated his experience in designated questionnaires. Results: Ten expandable cages of various sizes were implanted according to trial measurements obtained during the procedure. Surgeons successfully inserted, positioned and expanded the cages based on surgical technique. The procedure was reported as being easy to perform by the surgeons. Implant positioning was consistently accomplished in the anterior two-thirds of the disc space near the apophyseal ring due to the articulated feature covering a large footprint. Gradual cage angular expansion was performed till the maximal degree allowed in all cases, customized to each level treated. Analysis of dissected cadavers revealed an effective discectomy with preservation of the annulus except the entry portal. No endplate violation was reported in all specimens. On lateral X-rays, lordotic increment from preoperative values was significantly higher in L2–3 discs, being 7.8°±2.2 (from 5 to 10°). On L5-S1 discs the increase was 4.8°±1.3 (from 4 to 7°). The overall added lordotic correction was on average 12.6°±2.5 per spine. Conclusion: The use of 3-dimensional expandable cages in this cadaver study allowed better endplate bone contact with a well-fitted adjustment, according to the level treated without endplate damage. Lordosis correction was achieved differentially depending on the level and original values of alignment. Added up individual correction was shown on overall sagittal correction using two cages, which would be likely enhanced with facet resection and posterior instrumentation. The use of well positioned, large footprint, expandable lordotic correcting cages may lead to a more biomechanically balanced results in lumbar spine fusion.